PREDICTION OF COMPRESSION AND EXTENSION ZONES IN GEOLOGICAL STRUCTURES BASED ONLY ON THE VELOCITIES OF LONGITUDINAL WAVES IN THE GEOLOGICAL MEDIUM - B. P. Sibiryakov; E. A. Khogoev (Геодинамика и тектонофизика)
The article presents accurate solutions for the problem for two elastic half‐spaces with an arbitrary curvilinear interface. Our study shows that dilatation solutions (Poisson integrals) are dependent on neither an overall compression modulus nor the Poisson ratio, and depend only on the velocity of longitudinal waves. These specific solutions can be supplemented by general solutions for an incompressible elastic medium, and the boundary conditions of the rigid contact for the sum of the solutions can thus be satisfied. Relatively simple calculations make it possible to determine the divergence of the displacement field and reduce the entire problem solving process to a study of Poisson equations with a known divergence. Furthermore, predictions of volumetric compression or extension are important for geological investigations, since the zones characterized by reduced pressure rates may act as fluid attractors.